Rural Economic Development through ‘Basuduai’: A Model of Cattle Breeding Partnership in West Sumatera - Noveri Maulana Maulana; Anggun Pesona Intan Puspita (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2020)
The concept of ‘Basuduai’ on cattle breeding investment has been popularly implemented in West Sumatra for decades. Currently, this partnership modelling is still implemented in several villages and rural areas. This study aims to describe ‘basuduai’ as a socio-entrepreneurship approach in a simple descriptive method using the Business Model Canvas (BMC). Perhaps this model could also be implemented in other rural areas as an economic development approach. The data was collected through ten in-depth interviews and two focus group discussions (FGD) among the local partners in Payakumbuh, West Sumatra. Content and context analysis is conducted to describe the categorical theme for results analysis. The finding shows that cattle breeding investment as the 'Basuduai' system is an indigenous approach in the local community in West Sumatra. However, based on the business model canvas, the role of community leader should be prioritized to balance the system. Hence, the need for a formal socio entrepreneurship entity as the middleman should be developed. Perhaps, this study could contribute to the development of rural economic programs and could be replicated in other rural areas in Indonesia and also in other countries. Discussion and limitations are also stated in the study Keywords: Partnership Investment, Cattle Breeding, Business Model Canvas, Socio-Entrepreneurship, Economic Development, Economic EmpowermentJEL Clasification: L20, P32, R51